THE SCIENTIFIC APPROACH IN TEACHING SPEAKING FOR VARIOUS TEXTS (The Case of Three Teacher Candidates of Wiralodra University Indramayu in The Academic Year 2013/2014). (Universitas Negeri Semarang, 2014)
This study investigated the implementation of scientific approach in teaching speaking for various texts. It is aimed to describe and capture how teacher candidates implement scientific approach which consists of observing, questioning, exploring, associating and communicating in their teaching practice. What problems they faced during their teaching practice and how teacher candidates solve those problems.This studyuseda qualitative research design.The subjects of this study were three students of English Department of Wiralodra University who were doing teaching practice (PPL). Triangulation was used to validate the data. The findings showed that the three teacher candidates had implemented scientific approach in their teaching speaking although there still a lot of imperfectness and it can be concluded that between 1st, 2nd, and 3rd teacher candidates, the 3rd was the best to implement the scientific approach. The three teacher candidates also found problems in their teaching such as many students were hardly to speak English directly because of the vocabulary and lack of practice. However, both teacher candidates were able to solve the problem by peer error correction.